What Kind of Democracy for European Union? - Švarplys, Andrius (Sociologija. Mintis ir veiksmas, 2010)
According to the ‘standard version’ of democratic deficit, European Union suffers from the lack of legitimacy comparing with the national democratic system. The efforts were stated to raise European Parliament’s strength as the main political body representing people’s will and to promote European political community. This idea normatively and empirically confronts the arguments that European Union still bears exclusively economic (regulatory) character meanwhile national democratic systems assure that European institutional bodies meet democratic requirements. The problem of EU democracy seems to stand in the center of political debate what kind of political system is preferred: federation, intergovernmental, or intermixed sui generis political system. Each of these approaches defines the particular meaning of democracy in the European Union.
Keywords: European Union; democratic deficit; G. Majone; A. Moravcsik; democracy